Electrostatic control of half-site spacing preferences by the cyclic AMP response element-binding protein CREB - Montclare, Jin Kim (Oxford University Press, 2001)
Basic region leucine zipper (bZIP) proteins represent a class of transcription factors that bind DNA using a simple, dimeric, α-helical recognition motif. The cAMP response element-binding protein (CREB) is a member of the CREB/ATF subfamily of bZIP proteins. CREB discriminates effectively in vivo and in vitro between the 10 bp cAMP response element (ATGACGTCAT, CRE) and the 9 bp activating protein 1 site (ATGACTCAT, AP-1). Here we describe an alanine scanning mutagenesis study designed to identify those residues within the CREB bZIP element that control CRE/AP-1 specificity. We find that the preference of CREB for the CRE site is controlled in a positive and negative way by acidic and basic residues in the basic, spacer and zipper segments. The CRE/AP-1 specificity of CREB is increased significantly by four glutamic acid residues located at positions 24, 28, 35 and 41; glutamic acid residues at positions 10 and 48 contribute in a more modest way. Specificity is decreased significantly by two basic residues located at positions 21 and 23; basic residues at positions 14, 18, 33 and 34 and V17 contribute in a more modest way. All of the residues that influence specificity significantly are located on the solvent-exposed face of the protein–DNA complex and likely participate in interactions between and among proteins, not between protein and DNA. The finding that the CRE/AP-1 specificity of CREB is dictated by the presence or absence of charged residues has interesting implications for how transcription factors seek and selectively bind sequences within genomic DNA.